2017
DOI: 10.21037/jtd.2017.08.71
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of video-assisted thoracoscopic surgery esophagectomy for esophageal cancer: a propensity score-matched analysis

Abstract: Results: Matching based on propensity scores produced 42 patients in each group for the analysis.After propensity matching, there were only two operative mortalities in the OE group, and both died of postoperative pneumonia. The overall incidence of postoperative complications was 38.1% (16 of 42) and 57.1% (24 of 42) in the VE group and in the OE group, respectively (P=0.088). The incidence of pulmonary complications was lower in the VE group than in the OE group (9.5% vs. 40.5%, P=0.004). The 2-year overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Moon et al observed a longer operating time when performing thoracoscopical esophagectomy compared to a classical approach, but significantly less respiratory complications (9.5% vs. 40.5%, P=0.004) (ref. 22 ). Growing experience with minimally invasive esophagectomy has been associated with a decrease in postoperative respiratory complications [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al observed a longer operating time when performing thoracoscopical esophagectomy compared to a classical approach, but significantly less respiratory complications (9.5% vs. 40.5%, P=0.004) (ref. 22 ). Growing experience with minimally invasive esophagectomy has been associated with a decrease in postoperative respiratory complications [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…(42,43). The overall pulmonary complications are described to be as high as 40.5% for OE compared to 9.5% for MIE (p=0.004) in some studies (44). Especially pneumonia has a signi cant negative impact on survival (p = 0.035) with a multivariate HR of 1.456 (([CI]: [1.020; 2.079]) p= 0.039).…”
Section: Discussionmentioning
confidence: 99%
“…The primary analysis will test the following hypotheses: (42,43). The overall pulmonary complications are described to be as high as 40.5% for OE compared to 9.5% for MIE (p = 0.004) in some studies (44). Especially pneumonia has a signi cant negative impact on survival (p = 0.035) with a multivariate HR of 1.456 (([CI]: [1.020; 2.079]) p= 0.039).…”
Section: Data Managementmentioning
confidence: 99%